Effect of Friction Stir Welding and Friction Stir Processing Parameters on The Efficiency of Joints - Al-Shammari, Mohsin Abdullah; Ibrahim, Worood H. (Al-Nahrain Journal for Engineering Sciences, 2018)
Friction Stir Welding is one of the most practical welding process at the solid state. Friction Stir Processing is used to enhance the microstructure of FSW welded zone. The present study investigates the effect of welding parameters on the tensile properties of FSW and FSP joining 3 mm AA 5083 - H111 aluminum alloy by means of stress – strain curve with a uniaxial tensile test and by comparing the efficiency between FSW , FSP and base metal .The experiments were conducted with 1000,1500 and 2000 rpm rotation speeds ,and 20,40 and 60 mm/min travel speed. The best result of the welding joint was shown at the 20 mm/min feed speed and 1500 rpm rotational speed for FSW, and 40 mm/min feed speed and 1500 rpm rotation speed for FSP. The efficiency of ultimate tensile strength reaches to 92% for FSW and 94% for FSP.